A complex interplay between Akt, TSC2 and the two mTOR complexes. (20th January 2009) - Huang, Jingxiang; Manning, Brendan D.
Abstract : Akt/PKB (protein kinase B) both regulates and is regulated by the TSC (tuberous sclerosis complex) 1–TSC2 complex. Downstream of PI3K (phosphoinositide 3-kinase), Akt phosphorylates TSC2 directly on multiple sites. Although the molecular mechanism is not well understood, these phosphorylation events relieve the inhibitory effects of the TSC1–TSC2 complex on Rheb and mTORC1 [mTOR (mammalian target of rapamycin) complex] 1, thereby activating mTORC1 in response to growth factors. Through negative-feedback mechanisms, mTORC1 activity inhibits growth factor stimulation of PI3K. This is particularly evident in cells and tumours lacking the TSC1–TSC2 complex, where Akt signalling is severely attenuated due, at least in part, to constitutive activation of mTORC1. An additional level of complexity in the relationship between Akt and the TSC1–TSC2 complex has recently been uncovered. The growth-factor-stimulated kinase activity of mTORC2 [also known as the mTOR–rictor (rapamycin-insensitive companion of mTOR) complex], which normally enhances Akt signalling by phosphorylating its hydrophobic motif (Ser 473 ), was found to be defective in cells lacking the TSC1–TSC2 complex. This effect on mTORC2 can be separated from the inhibitory effects of the TSC1–TSC2 complex on Rheb and mTORC1. The present review discusses our current understanding of the increasingly complex functional interactions between Akt, the TSC1–TSC2 complex and mTOR, which are fundamentally important players in a large variety of human diseases.